Impact of incentives on COVID-19 vaccination; A systematic review - Mardi, Parham; Djalalinia, Shirin; Kargar, Reza; Jamee, Mahnaz; Esmaeili Abdar, Zahra; Qorbani, Mostafa (Frontiers in Medicine, 2022)
Introduction: Although vaccination is the most effective way to limit and overcome the COVID-19 pandemic, a considerable fraction of them are not intended to get vaccinated. This study aims to investigate the existing research evidence and evaluate the effectiveness and consequences of all incentives provided for increasing the uptake of COVID-19 vaccination. Methods: A systematic search in PubMed, Web of Science (WoS), and SCOPUS from 2020 until October 10, 2021, was conducted on experimental studies evaluating the effects of incentives including cash, lottery voucher, and persuasive messages on COVID-19 vaccination intention and uptake. The study selection process, data extraction, and quality assessment were conducted independently by two investigators using Consolidated Standards of Reporting Trials (CONSORT 2010) checklist. Results: Twenty-four records were included in the qualitative analysis. Most of the included studies assessed the effect of financial incentives. In fourteen studies (58%) the assessed outcome was vaccination uptake and in nine (37.5%) others it was vaccination intention. One study considered self-reported vaccination status as the outcome. This study shows that high financial incentives and the Vax-a-million lottery are attributed to a higher vaccination rate, while the low amount of financial incentives, other lotteries, and persuasive messages have small or non-significant effects. Conclusion: Paying a considerable amount of cash and Vax-a-million lottery are attributed to a higher vaccination. Nevertheless, there is a controversy over the effect of other incentives including other lotteries, low amount of cash, and messages on vaccination. It is noteworthy that, inconsistency and imprecision of included studies should be considered.